2021
DOI: 10.1111/jnc.15518
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid levels of L‐glutamate signal central inflammatory neurodegeneration in multiple sclerosis

Abstract: Excessive extracellular concentrations of L‐glutamate (L‐Glu) can be neurotoxic and contribute to neurodegenerative processes in multiple sclerosis (MS). The association between cerebrospinal fluid (CSF) L‐Glu levels, clinical features, and inflammatory biomarkers in patients with MS remains unclear. In 179 MS patients (relapsing remitting, RR, N = 157; secondary progressive/primary progressive, SP/PP, N = 22), CSF levels of L‐Glu at diagnosis were determined and compared with those obtained in a group of 40 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 53 publications
7
19
0
Order By: Relevance
“…In this regard, glutamate levels in hippocampal, thalamic, and cingulate regions have been associated with visual–spatial memory in MS patients ( n = 80), suggesting that glutamatergic system imbalance may affect memory function in MS. Another study demonstrated a slight reduction of cerebrospinal fluid (CSF) levels of l -glutamate ( l -Glu) and inflammatory neurodegeneration in MS patients. Importantly, altered expression of l -Glu was associated with disability progression, oxidative stress, and inflammation in this study . These results suggest that l -Glu in the CSF may be a promising biomarker of inflammatory neurodegeneration in MS.…”
Section: Amino Acid Neurotransmitterssupporting
confidence: 61%
See 1 more Smart Citation
“…In this regard, glutamate levels in hippocampal, thalamic, and cingulate regions have been associated with visual–spatial memory in MS patients ( n = 80), suggesting that glutamatergic system imbalance may affect memory function in MS. Another study demonstrated a slight reduction of cerebrospinal fluid (CSF) levels of l -glutamate ( l -Glu) and inflammatory neurodegeneration in MS patients. Importantly, altered expression of l -Glu was associated with disability progression, oxidative stress, and inflammation in this study . These results suggest that l -Glu in the CSF may be a promising biomarker of inflammatory neurodegeneration in MS.…”
Section: Amino Acid Neurotransmitterssupporting
confidence: 61%
“…Importantly, altered expression of L-Glu was associated with disability progression, oxidative stress, and inflammation in this study. 34 These results suggest that L-Glu in the CSF may be a promising biomarker of inflammatory neurodegeneration in MS.…”
Section: Amino Acid Neurotransmittersmentioning
confidence: 87%
“…Furthermore, clinical studies also showed that abnormally greater cerebrospinal fluid (CSF) levels of pro‐inflammatory cytokines are associated with severe alterations in excitatory synaptic transmission and plasticity and with a higher risk of disease progression in MS patients (Rossi et al, 2012, 2014; Stampanoni Bassi et al, 2019, 2020). In line with this, independent findings unveiled the existence of a direct correlation between pro‐inflammatory cytokines and L‐glutamate (L‐Glu) concentrations in the CSF of MS patients (Kostic et al, 2014; Stampanoni Bassi et al, 2021), further suggesting that excitatory synaptic transmission and neuroinflammatory processes are intimately linked in a complex dynamic interaction that contributes to MS clinical phenotypes and disease progression (Levite, 2017).…”
Section: Introductionmentioning
confidence: 88%
“…Similarly, studies into neuroinflammation and neuroimmunology are a growing area within the journal, such that in 2021 we published a special issue dedicated to this topic (https://onlinelibrary.wiley.com/toc/14714159/2021/158/1). Examples of recent original articles in this area include preclinical studies in rodent models of multiple sclerosis (Tezuka et al, 2022) through to human studies assessing in the cerebrospinal fluid of patients for neurochemical markers of inflammation in neurodegeneration (Stampanoni Bassi et al, 2021).…”
Section: Figurementioning
confidence: 99%
“…Examples of recent original articles in this area include preclinical studies in rodent models of multiple sclerosis (Tezuka et al, 2022) through to human studies assessing in the cerebrospinal fluid of patients for neurochemical markers of inflammation in neurodegeneration (Stampanoni Bassi et al, 2021).…”
mentioning
confidence: 99%